: Analisis Persebaran Intensintas Penerangan Di Laboratorium Balai Keselamatan Dan Kesehatan Kerja (K3) Samarinda Berdasarkan PERMANKER No. 5 Tahun 2018 Menggunakan Metode Mapping - Hasmah, Siti; Munir, Rahmiati; Djayus, Djayus; Putri, Erlinda Ratnasari (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2024)
A light is needed by humans to recognize an object visually. Good lighting allows people to see the objects they are working on clearly and quickly. There is a national standardization that is used as a race for the intensity of lighting that is categorized based on the type of work performed. Therefore, this study aims to determine the level of intensintas lighting in the Laboratory of the Center for Occupational Safety and health (K3) Samarinda based PERMENAKER No. 5 of 2018. In this study using the mapping method used as the determination of the coordinate points and then use the Lux meter EC 1 and Laser Meter Distance for data retrieval illumination. The results obtained the intense level of illumination in the Laboratory of the Center for Occupational Safety and health (K3) Samarinda based on PERMENAKER No. 5 of 2018 (lighting standards according to job classification) the work areas that meet the standards are on the administration workbench, pretreatment table (Room 8), and fume hood laying room (Room 7) while the work areas of the weighing room (Room 1), UV-VIS room (Room 2), Spectrophoto room (Room 3), Natural absorption room (Room 4), and solid chemical room (Room 5) did not meet the standards.